SUSTAINABILITY ACCOUNTING AND STOCK PERFORMANCE OF QUOTED CONSUMER GOODS MANUFACTURING FIRMS (Journal of Global Accounting, 2023)
The broad objective of the paper is to evaluate the effect of sustainability accounting on stock performance of quoted consumer goods manufacturing firms in Nigeria. The study utilized the ex-post facto research design. The sample comprised twenty two quoted consumer goods manufacturing firms on the Nigerian Stock Exchange. The study relied on secondary data obtained from annual report and accounts from 2011 to 2018. The proxy for sustainability accounting was measured with social and economic measures while stock performance was measured using share prices and earnings per share. The hypotheses were tested using Ordinary Least Square (OLS) regression at 5 per cent significance level. The results revealed that proxies of sustainability accounting had a significant effect on share prices and earnings per share at 5%. The study recommended amongst others that to the issue of sustainability accounting should be part of the corporate mission and strategy statements and not just be regarded as a philanthropic exercise. Policy makers are further encouraged to develop standards to gauge social responsibility disclosure and performance.
Keywords: Sustainability Accounting; Share Price; Earnings per Share